Welcome to the future : skills and tools necessary to face the challenges of a new life - Ogunleye, Akintunde I. (Abuja: Universal Communications Press, 2004)
The book is targeted at the "Nigerian Tertiary Graduate", it contains practical life functional tools and skills necessary to succeed in a society plagued by uncertainties and other social vices. This book is based on workshops and lectures that have aided thousands of people across the world to scale the heights. The author takes supposedly complex issues of life and breaks them down into simple ABC that can be comprehended easily -- Back Cover.
A Hand Book for the Nigerian Tertiary Graduate
rpm 01/09/16
Loans
Keywords: Personal improvement; Social skills and tools; Success --- applied psychology; Tertiary graduates; Nigeria